Role of the processing pore of the ClpX AAA+ ATPase in the recognition and engagement of specific protein substrates - Siddiqui, Samia M. (Cold Spring Harbor Laboratory Press, 2004)
ClpX binds substrates bearing specific classes of peptide signals, denatures these proteins, and translocates them through a central pore into ClpP for degradation. ClpX with the V154F pore mutation is severely defective in binding substrates bearing C-motif 1 degradation signals and is also impaired in a subsequent step of substrate engagement. In contrast, this mutant efficiently processes substrates with other classes of recognition signals both in vitro and in vivo. These results demonstrate that the ClpX pore functions in the recognition and catalytic engagement of specific substrates, and that ClpX recognizes different substrate classes in at least two distinct fashions.